Rozwój Wielonarodowego Korpusu Północno-Wschodniego (MNC NE) i jego rola w kształtowaniu bezpieczeństwa flanki wschodniej NATO .......... 59 - Wojtaszak, Andrzej (Bezpieczeństwo regionalne: Węzłowe problemy i procesy, 2020)
The 70th anniversary of the creation of the North Atlantic Pact and the 20th anniversary of Poland’s presence in the structures of the Alliance allow us to present the current balance sheets. The Polish presence in NATO is accompanied by an increase in the importance and credibility of the Polish Army as an integral part of the Alliance. An important element of cooperation is the Multinational Corps Northeast based in Szczecin. Since 2014 (at the Newport Summit), NATO’s “Readiness Action Plan” has decided to increase its activity on the Alliance’s eastern flank. It was decided to create the NATO Response Forces and to establish the Very High Readiness Joint Task Force (VJTF) – a force capable of responding quickly. It was the Alliance’s response to an increased threat from Russia. In 2016, MNC NE became a NATO high preparedness unit. Currently, the Corps consists of 380 officers from 25 countries (including Finland and Sweden from outside the Alliance). MNC NE Headquarters in Szczecin is NATO’s highest command in the Baltic Sea region. Since June 2017, it has been operating as the High Readiness Command, which means that it is responsible for all NATO units and land forces located on the eastern flank, starting with NATO Force Integration Units and ending with the structures of the so-called advanced reinforced presence (idea of group B9).